Barriers and facilitators to dental care during pregnancy: a systematic review and meta-synthesis of qualitative studies - Juliana Schaia Rocha; Letícia Arima; Ana Cláudia Chibinski; Renata Iani Werneck; Samuel Jorge Moysés; Márcia Helena Baldani (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Some barriers to dental treatment during pregnancy are poorly understood, especially those related to psychosocial factors, which are better explored in qualitative studies. The aim of this systematic review was to explore the barriers and facilitators to dental care during pregnancy through a thematic synthesis of qualitative studies. Qualitative or mixed-methods studies published in English, Portuguese, Spanish and French, from 2000 to 2016, were included. The search strategies were conducted in PubMed, Scopus, Web of Science, LILACS, BBO and CINAHL. To evaluate the quality of the studies, we used the Critical Appraisal Skills Programme tool. Thematic synthesis was performed in order to interpret and summarize the results. From 2,581 screened studies, ten were included in the synthesis. We found 14 analytical themes related to barriers and facilitators to dental care during pregnancy that interacted in complex ways: physiological conditions, low importance of oral health, negative stigma regarding dentistry, fear of/anxiety toward dental treatment, mobility and safety, financial barriers, employment, time constraints, social support, lack of information, health professionals' barriers, family and friends' advice, beliefs and myths about the safety of dental treatment. Myths and beliefs about oral health and dental treatment during pregnancy appear to be the most frequent barriers, both to pregnant women and to dentists or other health professionals. The findings of this review may support new studies, especially to test intervention protocols and to guide effective public policies for the promotion of oral health during pregnancy.